PERANAN KONSERVATISME PADA INFORMATION ASYMMETRY: SUATU TINJAUAN TEORETIS - BUDIASIH, I G.A.N. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011), 2011)
Conservatism is one of mechanisms of corporate governance that could reduce managers’ capability to manipulate and overstate financial report, especially financial performance, so cash flow and company’s value could be increased. Conservatism is also important in decreasing agency cost and increasing the quality of financial information to increase company’s value and the share price. Financial statement employing principle of conservatism could reduce management chance to manipulate financial report and decrease deadweight loss as an agency cost emerged due to information asymmetry. Thus it can be said that conservative financial statement could reduce information asymmetry. Information asymmetry can be handled by forcing management to fully disclose the company’s condition on the financial statement. Another way is to monitor management conduct by employing independent auditor.
Keywords: conservatism, corporate governance, agency cost, information asymmetry